An Evaluation of Short Term Greenhouse Gas Emissions from Soil and Atmosphere Exchange in Response to Controlling Edaphic Factgors of Eucalyptus Plantation, Gujarat, India - Kumar, Nirmal; Meghabarot, JI; Gupta, Priyakanchini; Patel, Kanti (International Journal of Environment, 2014)
A considerable amount of atmospheric GHG is produced and consumed through soil processes. Soils provide the largest terrestrial store for carbon (C) as well as the largest atmospheric CO2 sources through autotrophic and heterotrophic organisms. Soils are also the greatest source (∼60%) of CH4 and N2O through microbially mediated processes of methanogensis, nitrification and denitrification. Short term CO2, CH4 and N2O gas fluxes from soil under a Eucalyptus plantation in central Gujarat, Western India were measured for three month duration (February to April, 2013) at fifteen days interval using closed static chamber technique and gas chromatography method. Simultaneously soils were analyzed at 0.0-10, 10-20, and 20-30 cm depth for pH, conductivity, organic carbon, nitrogen, phosphate, sulphate to correlate with gas emissions. The results showed that the soil in our study was a sink of atmospheric CO2, CH4 and N2O which the flux varied from -65.27 to 14.6, -0.005 to 0.07 and -0.03 to 0.33 mg m-2 h-1respectively. CO2 emissions were found maximum as compared to other two gases. Variations in soil N2O emissions could be primarily explained by litter C:N ratio and soil total N stock. Differences in soil CH4 uptake could be mostly attributed to the soil CO2 flux and water filled pore space (WFPS). Soil C:N ratio could largely account for variations in soil CO2 emissions. A strong positive relationship existed between CH4 flux and soil temperature. The N2O flux correlated with WFPS and the global warming potential of N2O is highest compared to other two principal gases. DOI: http://dx.doi.org/10.3126/ije.v3i3.11064 International Journal of Environment Vol.3(3) 2014: 59-77